Study the Effect. Extracts and Inhibitory Potency of Plant Capparis Spinosa on Breast Cancer Cells - Amjed Abbawe Salih1 , Thamer Esmail Ahmed2 , Diaa Mahmoud Nigam3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of this study is to analyze Capparis spinosa and the principal constituent substance in Iraq which isrecognized by NMR experimentations and the key constituent identified by NMR is Stachydrine. Capparisspinosa is descended from the family (Capparidaceae) and is described as a herbaceous plant with simpleleaves together edge and forked ears and bear flowers on long necks and fruits pear shape. Capparis containsbitter materials, claycosides, enzymes, mayonnaise, acetic acid, bric, soap and volatile oils with a smellsimilar to the smell of garlic, as well as sulfuric klycosides. All parts of plants used as a treatment as rootsthat are used as a diuretic and leg used as a dentin for diarrhea as well as fruit is used as a treatment for cancerWe observe measurements of significant decrease in the level of breast cancer cells at? 0.05